Serum estradiol level on the day of ovulation trigger and pregnancy outcomes in in-vitro fertilisation-intracytoplasmic sperm injection cycles - Pillai, Avani; T., Fessylouis; P., Ramesh; T., Parvathy; N., Aparna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: There is conflicting evidence with regards to the impact of supraphysiologic estradiol levels in in-vitro fertilisation-intracytoplasmic sperm injection (IVF-ICSI) cycles on pregnancy outcomes such as oocyte quality, implantation, and clinical pregnancy. The objective of our study was to evaluate the effect of serum estradiol levels on the day of ovulation trigger on pregnancy outcomes in IVF-ICSI cycles. Methods: We performed a retrospective cohort study, which included eighty-three women who underwent IVF-ICSI and experienced fresh embryo transfer (ET) over one year period. The women included in the study were divided into four groups according to the serum estradiol level on the day of ovulation trigger; Group I: <2000pg/ml, Group II: 2000-3000pg/ml, Group III: 3000-4000pg/ml and Group IV: >4000pg/ml. The outcome measures including number of oocytes retrieved, MII (metaphase II) oocytes, fertilization rate, embryo quality, overall pregnancy rate, implantation rate and clinical pregnancy rate were compared among these four groups. Results: The total number of oocytes, MII oocytes as well as good quality embryos significantly increased from group 1 to group 4. The implantation rate was lowest in group 4 compared to all other groups, although not statistically significant. There was no significant difference in overall and clinical pregnancy rate between the groups. Conclusions: Serum estradiol level shows a positive correlation with the number of oocytes retrieved and good quality embryos. A higher estradiol level does not have a significant negative impact on the implantation rate, overall or clinical pregnancy rate.